Verses and Voices: Exploring Teachers’ Lived Experiences in ESL Poetry Instruction (The Journal of DMC, 2026)
Poetry is one of the learning resources for basic-level English students in Nepal. This qualitative phenomenological study explores teachers’ experiences of teaching English poetry in basic schools in Nepal. Through semi-structured interviews with five participants, this study investigated teachers’ perceptions of the usefulness of poetry in English language learning, their pedagogical practices, challenges, and the expected support required to enhance poetry teaching at the basic level. The data were analyzed thematically, following an inductive coding procedure. This study found that the teachers perceive poetry as beneficial for fostering creativity, enriching vocabulary, enhancing speaking skills, and encouraging active classroom participation. The teachers followed traditional teacher-centered methods, primarily engaging students in analytical activities provided in the textbook. However, teachers encounter significant barriers in teaching poetry, including students’ limited language proficiency, unfamiliar vocabulary, and the figurative language used in poetry. This study indicated that institutional support for using ICT tools in teaching and learning, customized training for poetry teaching, and collaboration among teachers can enhance poetry instruction. These findings are relevant for educators and policymakers aiming to meaningfully integrate literature into ESL classrooms.